The Applicability of Augmented Reality Technologies for Evaluating Learning Activities - Talgat Sembayev (Kassel University Press, 2021)
a new trend in the development of immersive technologies has become augmented reality (AR), which is in demand due to its property to implement visual objects to enrich the learning content. The paper is devoted to the study of the applicability of AR technologies for evaluating learning activi-ties since there is a problem of inconsistency of teaching approaches with tools that lead to biased results. This led to the development of the “AR Quiz” application that contains interaction types such as touch-based, voice, input field, gaze and gesture that stimulate activities. In combination with 10 other forms of assessment materials, its application field has expanded and the tasks for students have diversified. The present study provides the calculation of validity and reliability coefficients of the assessment materials contained in the “AR Quiz” application that reflects the suitability of indicators for the purpose, accuracy and stability of measurements. The paper reveals positive attitudes of expert teachers and students towards the use of AR when evaluating learning activities. Along with integration map of compliance of AR interaction types with assessment materials, the paper provides recommendations for teachers on evaluating learning activities based on AR.